ANALYSIS OF HUMAN CAPITAL INVESTMENT AND INCOME INEQUALITY IN INDONESIA - Natasya Rahmayuli Irwin; Yulia Anas (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study examines the heterogeneous effects of human capital investment—encompassing education, job training, health, and technology—on income inequality across districts and cities in Indonesia. Using individual microdata from the 2023 National Labor Force Survey (Sakernas) and the National Socio-Economic Survey (Susenas), the data are aggregated to the district/city level to capture regional disparities in income distribution. The analysis employs multiple linear regression with robust standard errors to address heteroscedasticity inherent in aggregated data. The empirical results indicate that regional health conditions are associated with significantly lower income inequality, while job training participation and technology adoption exhibit positive and significant relationships with inequality. These findings challenge the conventional assumption that all forms of human capital investment uniformly reduce inequality and instead highlight a “digital paradox,” whereby unequal regional access to skills development and technology intensifies income disparities. This study contributes to the literature by identifying job training and technology as potential drivers of inequality in the absence of inclusive regional access. The policy implications underscore the importance of targeted vocational programs and equitable digital infrastructure development in underdeveloped regions